Environmental, Social, and Governance Disclosure and Firm Value - Winona Adelia Bianda Pangaribuan; I Putu Sudana (International Forum of Researchers and Lecturers, 2025)
This study aims to obtain empirical evidence regarding the effect of Environmental, Social, and Governance (ESG) disclosure on firm value. The research sample was obtained using purposive sampling on mining firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, with a total of 102 observations. Data analysis was conducted using panel data regression to test the proposed hypotheses. The results show that environmental disclosure has a significant positive effect on firm value, while social and governance disclosure have a significant negative effect. The theoretical implication of this study refers to agency theory, which asserts that information transparency through ESG can reduce information asymmetry between management and shareholders. However, if disclosure is carried out merely as a formality or symbolic practice, it may instead generate agency costs that are detrimental to the firm. In addition, these findings are also relevant to signaling theory, in which environmental disclosure can serve as a positive signal of a firm’s commitment to sustainability practices, thereby enhancing investor trust and strengthening the firm’s reputation. Practically, this study contributes to providing a more comprehensive understanding for firms, management, investors, and other stakeholders, while also serving as a reference for future research on ESG and firm value.